FRI0243 Extent of disease on high-resolution CT lung is a predictor of decline and mortality in systemic sclerosis-related interstitial lung disease. (23rd January 2014) - Moore, O.A.; Goh, N.; Corte, T.; Rouse, H.; Hennessy, O.; Thakkar, V.; Byron, J.; Sahhar, J.; Roddy, J.; Youssef, P.; Nash, P.; Zochling, J.; et al.
Abstract : Objectives: We sought to determine whether the extent of disease on high-resolution CT lung (HRCT), measured using a simple grading system, [1] is predictive of decline and mortality in systemic sclerosis-related interstitial lung disease (SSc-ILD), independently of pulmonary function tests (PFTs) and other prognostic variables. Methods: SSc patients with a baseline HRCT performed at the time of ILD diagnosis were identified. All PFTs performed during follow-up were retrieved. Demographic and disease-related data were prospectively collected. HRCTs were graded according to the percentage of lung disease seen; >20% - extensive, <20% - limited, unclear - indeterminate. Indeterminate HRCTs were converted to limited or extensive using an FVC threshold of 70%. The composite outcome variable was deterioration (defined as need for home oxygen or lung transplantation), or death. Results: Among 172 patients followed for mean±SD of 3.47±2.93 years, there were 33 outcome events. Figure 1 shows a Kaplan-Meier survival curve of HRCT score against survival. Survival estimates were significant for two raters and approached significance for the third (log-rank p<0.0001, p=0.0005, p=0.13). In Weibull multivariable hazards regression modelling, baseline HRCT grade was independently predictive of outcome, with an adjusted hazard ratio (aHR) =3.0, 95% CI: 1.2-7.5, p=0.02. Conclusions: Extensive changes (>20%) on HRCT at baseline, reported using a semi-quantitative grading system, are associated with a three-fold increased risk of deterioration or death in SSc-ILD, compared with limited changes. References: Goh NSL, Desai SR, Veeraraghavan S, et al. Interstitial Lung Disease in Systemic Sclerosis: A Simple Staging System. American Journal of Respiratory and Critical Care Medicine 2008;177:1248–1254. Disclosure of Interest: None Declared